Rock Squeezing Analysis in Young Mountains: A Case Study of Headrace Tunnel of Supermadi Hydroelectric Project in Nepal - Joshi, Dev Raj; Panthee, Suman (Himalayan Journal of Applied Science and Engineering, 2023)
The tunnel stability was assessed by analysing stress in the opening. Squeezing is the major problem faced while excavation a tunnel alignment in Himalayan region. This research was done in Super Madi hydroelectric project of 44 MW, in which main focus on the rock mass section of headrace tunnel of Inverted D shaped. The prediction of squeezing is done using various empirical, semi empirical, semi analytical and numerical modeling for the three different rock class. Finite element analysis was done using Rock science Phase2 software and output was verified by site investigation. The main lithologies of the area along the tunnel axis are banded gneiss. Based on the site condition, this study recommend the accurate method of predicting rock squeezing in the lesser Himalayan region with similar site conditions. It is found that the higher deformation occurs in high tunnel depth with low Q value.